In Pursuit of Right and Justice : Edward Weinfeld as Lawyer and Judge. - Nelson, William E. (William Edward), 1940- (NYU Press, 2004)
In Pursuit of Right and Justice chronicles the life of the United States District Court's Judge Edward Weinfeld, from his humble Lower East Side origins to his distinction as one of the nation's most respected federal judges. Judge Edward Weinfeld's personal growth and socio-economic mobility provides an excellent illustration of how Catholics and Jews descended from turn-of-the-century immigrants were assimilated into the mainstream of New York and American life during the course of the twentieth century. Weinfeld left a rich collection of personal papers that William E. Nelson examines, whic.